PENGEMBANGAN ALAT BANTU JALAN (WALKER) DENGAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) - Djumhariyanto, Dwi (JURNAL FLYWHEEL, 2016)
Along with growth of product will always experience of the innovation as according to its consumer requirement. For normal human being, its people whoever, of course have ready to accept the new circumstance in each;every its life process and try to adapt to the condition environment. Not rarely among those who are difficult walk, that matter caused downhill muscle strength of member move the. Assistive appliance walke even also become one of precise solution. One of assistive Appliance walke is Walker. Walker assistive appliance walke very light, easy to removed, waist-deep, made the than metal pipe, and this appliance provided with two functioning hilt as place used its consumer for the holding and also induing four sturdy foot as fulcrums. intake of consumer Data done by quesioner and processed to use the method of Quality Function Deployment (QFD), hence got some consumer desire Pursuant to the consumer desire development by creating some concept. From various developed concept, later then selected a concept pursuant to criterion like material substance, strong, rust proof and corrosion.